2019
DOI: 10.1089/bfm.2019.29128.kbm
|View full text |Cite
|
Sign up to set email alerts
|

ABM Clinical Protocol #31: Radiology and Nuclear Medicine Studies in Lactating Women

Abstract: A central goal of the Academy of Breastfeeding Medicine is the development of clinical protocols for managing common medical problems that may impact breastfeeding success. These protocols serve only as guidelines for the care of breastfeeding mothers and infants and do not delineate an exclusive course of treatment or serve as standards of medical care. Variations in treatment may be appropriate according to the needs of an individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In addition to clinical examination, many patients will undergo radiologic staging studies. Computed tomography with intravenous contrast or MRI with gadolinium contrast does not require an interruption in breastfeeding 36 (Level 4). Positron emission tomography and bone scintigraphy may require brief separation of the dyadfor 12 hours or up to 4 hours, respectively-during which time breast milk can be expressed and safely fed to infants 36 (Level 4).…”
Section: (Level 4)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to clinical examination, many patients will undergo radiologic staging studies. Computed tomography with intravenous contrast or MRI with gadolinium contrast does not require an interruption in breastfeeding 36 (Level 4). Positron emission tomography and bone scintigraphy may require brief separation of the dyadfor 12 hours or up to 4 hours, respectively-during which time breast milk can be expressed and safely fed to infants 36 (Level 4).…”
Section: (Level 4)mentioning
confidence: 99%
“…Computed tomography with intravenous contrast or MRI with gadolinium contrast does not require an interruption in breastfeeding 36 (Level 4). Positron emission tomography and bone scintigraphy may require brief separation of the dyadfor 12 hours or up to 4 hours, respectively-during which time breast milk can be expressed and safely fed to infants 36 (Level 4). These guidelines reflect the fact that radiotracers used in these studies are excreted in limited quantities into breast milk, but organs themselves will remain radioactive for a short period of time.…”
Section: (Level 4)mentioning
confidence: 99%
“…There is generally no need to stop breast feeding with other radiopharmaceuticals mentioned earlier. 28 Consultation with the nuclear physician is recommended when radionuclides are used in lactating women.…”
Section: Good Maternal Hydration and Frequent Voiding Can Resultsmentioning
confidence: 99%
“…It is critical that breastfeeding recommendations after radiology studies are evidence based and up to date to prevent any unnecessary interruption of breastfeeding. The current recommendations about the continuation of breastfeeding after radiologic imaging studies are summarized in the Academy of Breastfeeding Clinical Protocol #31 [5]. Radiation is used to obtain images in X-ray, mammography and CT studies.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation is used to obtain images in X-ray, mammography and CT studies. Radiation usage in these studies was shown to have no effect on breast milk, and the continuation of breastfeeding was recommended after these studies [5]. In iodinated contrast-enhanced CT, the systemic dose of contrast to the child is less than 0.01% of the maternal dose [5].…”
Section: Introductionmentioning
confidence: 99%